2021
DOI: 10.26786/1920-7603(2021)606
|View full text |Cite
|
Sign up to set email alerts
|

Conical flower cells reduce surface gloss and improve colour signal integrity for free-flying bumblebees

Abstract: Colour signals of flowers facilitate detection, spontaneous preference, discrimination and flower constancy by important bee pollinators. At short distances bees orient to floral colour patterns to find a landing platform and collect nutrition, potentially improving the plants’ reproductive success when multiple flowers are visited sequentially. In addition to pigments and backscattering structures within the petals’ internal layers, the epidermal micro-structure of the petals’ surface may also influence petal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…When floral pigment is concentrated in the epidermal layer at the side of viewing, the visual signal is more modulated and hence the flower more conspicuous than when pigment is distributed throughout the flower or in the epidermal layer on the other side (see figure 4 in van der Kooi et al 2016). In addition, the (surface) structure of the epidermal layer determines the degree of glossiness of a flower, with very flat and smooth surfaces creating a glossy (shiny) appearance, and cone-shaped epidermal cells a more matte appearance (van der Kooi et al 2014;Stavenga et al 2020;Wilmsen et al 2021). A comparative study covering 46 species in nine plant families revealed that, in general, the adaxial side of flowers is significantly more structured than the abaxial side (Kraaij & van der Kooi 2020).…”
Section: Spectral Characteristics Of Asymmetrically Coloured Flowersmentioning
confidence: 99%
See 1 more Smart Citation
“…When floral pigment is concentrated in the epidermal layer at the side of viewing, the visual signal is more modulated and hence the flower more conspicuous than when pigment is distributed throughout the flower or in the epidermal layer on the other side (see figure 4 in van der Kooi et al 2016). In addition, the (surface) structure of the epidermal layer determines the degree of glossiness of a flower, with very flat and smooth surfaces creating a glossy (shiny) appearance, and cone-shaped epidermal cells a more matte appearance (van der Kooi et al 2014;Stavenga et al 2020;Wilmsen et al 2021). A comparative study covering 46 species in nine plant families revealed that, in general, the adaxial side of flowers is significantly more structured than the abaxial side (Kraaij & van der Kooi 2020).…”
Section: Spectral Characteristics Of Asymmetrically Coloured Flowersmentioning
confidence: 99%
“…2020; Wilmsen et al . 2021). A comparative study covering 46 species in nine plant families revealed that, in general, the adaxial side of flowers is significantly more structured than the abaxial side (Kraaij & van der Kooi 2020).…”
Section: Spectral Characteristics Of Asymmetrically Coloured Flowersmentioning
confidence: 99%